Effects of project complexity on project success: the case of telecom firms in Nairobi - Kimaru, Joseph Mwangi (Strathmore University, 2019)
Project complexity is mentioned as one of the factors that both directly and indirectly influences project success and therefore an important factor to be managed along the project lifecycle. Complexity affects cost, time and quality objectives of a project, inhibits clear identification of goals and objectives, as well as influencing project planning and controlling practices. However, different forms of project complexities affect projects in different economic sectors differently. This study focused on investigating the effects of project complexity on project success. The study focused on project success in terms of project efficiency and organizational benefits. The study adopted a cross-sectional survey of telecom operators’ base in Nairobi, Kenya. The study used simple random and convenience sampling methods to select respondents from the target population. Data was collected using a structured questionnaire. Descriptive and inferential statistics were used establish the effect of project complexities on project success. Multiple linear regression showed that technological complexity positively influenced project efficiency but not organizational benefits. Organizational and environmental complexities positively influenced organizational benefits but not project efficiency. The study recommends that project implementers should find ways of streamlining technological, organizational and environmental complexities in order to influence project success.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Project complexity; Project success; Telecom firms